Desenvolvimento de um sistema eletrônico para monitoramento da eficiência de um catalisador SCR - Ferreira, Jéssimon (2022)
Catalysts are equipment used in motor vehicles, more precisely, in internal combustion vehicles and are integrated in the exhaust system of post combustion gases. In countries committed to preserving the environment, its use is promoted by law, because when activated, it can reduce by up to 98% the harmful gases generated by internal combustion caused by the air/fuel mixture. The reduction of harmful gases can impact the mitigation of cases of respiratory disease, mainly in the population of large urban centers. The choice of researching the influence of these gases in the diesel heavy-duty line is due to the fact that there is little research on the subject. In this context, this work presents the design and development of an electronic device capable of monitoring, through the temperature of the gases, the operation of an automotive catalyst for heavy-duty diesel vehicles. Monitoring has as its main objective the assessment of the state of operation of the catalytic device and purposely, being able to elaborate a timeline of the catalyst's functional life cycle. The variables temperature and NOx gases were carefully chosen for analysis. The SCR catalyst, object of study in this work, only activates after being subjected to a minimum initial temperature value and can reach its optimal value in the face of a chemical reaction between the post-combustion gases and the noble metals incorporated internally in the catalysts. This optimal value is of great relevance, as it is responsible for the decomposition of the urea that is injected parallel to the gases at the catalyst inlet. The decomposition of urea is responsible for the catalytic reduction of gases. Monitoring the functioning of the catalyst has the final motivation to assess whether the NOx gases are being converted at the output of the catalyst into H2O and N2.